A documentary study of Hendrik de Man, socialist critic of Marxism - Dodge, Peter, 1926-2021; Dodge, Peter, 1926-2021; Dodge, Peter, 1926-2021 (Princeton University Press, 1979)
In this collection of excerpts from the essential works of Hendrik de Man (1885-1953), Peter Dodge reinstates in historical consciousness this pioneer sociologist of the European socialist movement and of labor in industrial society. Regarded before World War II as pre-eminent among socialist theoreticians, comparable to Marx himself, de Man fell into obscurity when his equivocal neutralist stance during the Occupation of his native Belgium undermined his political legitimacy. Yet de Man's observations on the class order of capitalist society, on the difficulties of establishing effective ind.
Keywords: Socialism.; POLITICAL SCIENCE -- Political Ideologies -- Communism, Post-Communism & Socialism.; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism.; Socialism